2014
DOI: 10.1021/jp502401w
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Aggregation of Cysteine Functionalized Gold Nanoparticles

Abstract: The interaction of gold nanoparticles (AuNPs) with cysteine and its derivatives is the basis of a number of bionanotechnologies, and for these, the most important process is aggregation (or antiaggregation), which enables an array of colorimetric detection methods. When AuNPs were functionalized with cysteine, its dimer cystine, or the cysteine-derived tripeptide, glutathione, three different mechanisms of aggregation were observed. Both cysteine and glutathione induced aggregation of AuNPs without further pH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
63
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(78 citation statements)
references
References 59 publications
6
63
0
3
Order By: Relevance
“…This can be due to the formation of bridges between the nanoparticles and induction aggregation. Therefore, the induced AuNP aggregation by addition of L–Cys was attributed to the formation of zwitterionic networks involving interaction of the deprotonated carboxylate (‐COO − ) and protonated amine (‐NH 3 + ) groups between AuNPs‐bound to L–Cys, with the opposite groups of L–Cys capped on neighboring particles, consistent with studies conducted using FTIR spectroscopy and other techniques . Figure B shows the corresponding histogram providing the size distribution of AuNPs, indicating a normal distribution with a progressive increment of size from 9 nm to 14 nm.…”
Section: Resultssupporting
confidence: 76%
“…This can be due to the formation of bridges between the nanoparticles and induction aggregation. Therefore, the induced AuNP aggregation by addition of L–Cys was attributed to the formation of zwitterionic networks involving interaction of the deprotonated carboxylate (‐COO − ) and protonated amine (‐NH 3 + ) groups between AuNPs‐bound to L–Cys, with the opposite groups of L–Cys capped on neighboring particles, consistent with studies conducted using FTIR spectroscopy and other techniques . Figure B shows the corresponding histogram providing the size distribution of AuNPs, indicating a normal distribution with a progressive increment of size from 9 nm to 14 nm.…”
Section: Resultssupporting
confidence: 76%
“…This tendency is similar to the aggregation of AuNPs when cysteine was added to aqueous dispersion of AuNPs. 18 In contrast, when the total concentrations of Fmoc-VKVVC were increased to 0.125 and 0.25 mM, the absorbance of AuNPs at 530 nm was increased (Fig. 2g, inset).…”
Section: Redispersion Of Mnps With Cysteine-containing Peptidesmentioning
confidence: 94%
“…11 On the other hand, the shorter Fmoc-peptides, Fmoc-KVVC, Fmoc-VVC, Fmoc-VC and Fmoc-KC, as well as Fmoc-amino acid, Fmoc-C, hardly disperse the agglomerated MNPs. 18 Nonpeptide compound such as 1-dodecanethiol hardly exhibited redispersive property of AuNPs as well. Figure 5 shows schematic representation of possible mechanism of how the β-sheet redisperses the agglomerated MNPs.…”
Section: Influence Of Secondary Structure and Amino Acid Sequences Fomentioning
confidence: 99%
“…The peak position and FWHMs of N1 on NPs are in good correlation with the synthetic oxidized product without gold substrate and can be accordingly assigned to aromatic nitrogen atoms. Furthermore previous studies showed that N2 energy corresponds to zwitterionic/protonated amines, and in our case this suggests also the presence of tautomers. We noticed that the N s signal is, as expected, identical for both reaction conditions (RT and MW conditions), despite the pyTz stability differences.…”
Section: Methodsmentioning
confidence: 99%